2015
DOI: 10.1111/jnc.13081
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant adeno‐associated viral (rAAV) vectors mediate efficient gene transduction in cultured neonatal and adult microglia

Abstract: Microglia are a specialized population of myeloid cells that mediate CNS innate immune responses. Efforts to identify the cellular and molecular mechanisms that regulate microglia behaviors have been hampered by the lack of effective tools for manipulating gene expression. Cultured microglia are refractory to most chemical and electrical transfection methods, yielding little or no gene delivery and causing toxicity and/or inflammatory activation. Recombinant adeno-associated viral (rAAVs) vectors are non-envel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 73 publications
0
32
0
Order By: Relevance
“…One possible explanation could be that our AAV-SaCas9-GMF-sgRNA bears a modified capsid with a higher affinity for the selective transduction of neuronal cells. Previous studies have shown that amongst various AAV serotypes 2, 5, 6, 8 and 9 examined, AAV6 and AAV8 have significantly higher transduction efficiency in microglial cells [56]. Further microglial specificity can be achieved using either novel tropism modified and engineered AAV capsids, robust microglia specific promoter such as TMEM119 [57] and/or by employing neuronal detargeting by incorporating mir-124 target sequences in the AAV 3’UTR [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation could be that our AAV-SaCas9-GMF-sgRNA bears a modified capsid with a higher affinity for the selective transduction of neuronal cells. Previous studies have shown that amongst various AAV serotypes 2, 5, 6, 8 and 9 examined, AAV6 and AAV8 have significantly higher transduction efficiency in microglial cells [56]. Further microglial specificity can be achieved using either novel tropism modified and engineered AAV capsids, robust microglia specific promoter such as TMEM119 [57] and/or by employing neuronal detargeting by incorporating mir-124 target sequences in the AAV 3’UTR [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…An alternative strategy to modify microglia function is to modulate its phenotype by transgene expression in genetically modified animals (for a recent review see [ 317 ]). Alternatively, microglia can be modified by transfecting them with genes using various techniques [ 318 - 320 ], including viral infection [ 321 ]. It is important to consider that microglia are refractory to most chemical and electrical transfection methods, yielding little or no gene delivery and causing toxicity and/or inflammatory activation [ 320 , 322 ].…”
Section: Liposomes and Alternative Cargo Carriersmentioning
confidence: 99%
“…Alternatively, microglia can be modified by transfecting them with genes using various techniques [ 318 - 320 ], including viral infection [ 321 ]. It is important to consider that microglia are refractory to most chemical and electrical transfection methods, yielding little or no gene delivery and causing toxicity and/or inflammatory activation [ 320 , 322 ]. Previous studies with lentiviral vectors have shown effective gene transfer into microglia; however, lentiviral infection was associated with modest toxicity and mild inflammatory activation [ 320 ].…”
Section: Liposomes and Alternative Cargo Carriersmentioning
confidence: 99%
See 2 more Smart Citations